Pengaruh Shopeepaylater terhadap Daya Beli dan Perilaku Konsumtif Mahasiswa di Politeknik Piksi Ganesha Bandung - Deany Fitri, Tiara; Handari Adji, Widwi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research discusses the influence of Shopee PayLater (Spaylater) on the purchasing power and consumer behavior of students at the Piksi Ganesha Polytechnic in Bandung. Involving 101 respondents, this research used quantitative methods with validity, reliability, normality tests, and T and F tests to analyze the data. The research results show that Spaylater has a significant positive influence on students' purchasing power and consumer behavior. The validity and reliability test results show that the research instrument is valid and reliable. Statistical analysis, including T and F tests, supports these positive results. This research journal can help related parties, both academics and practitioners, in understanding the dynamics of using payment services such as Spaylater in managing purchasing power and managing consumer behavior among students.